New Media Strategies for Managing Digital Content in Educational Broadcasting - I Putu Astawa; Abdillah Rofiif Fatin Ritonga; Kailie Maharjan; Mahon Nitin (Journal of Social Science Utilizing Technology, 2025)
Background. In the digital age, educational broadcasting has become a key tool for delivering content to diverse audiences. The rapid development of new media technologies has transformed the way educational content is created, distributed, and consumed. However, managing digital content effectively remains a challenge for educational broadcasters, especially when it comes to adapting to evolving platforms and audience preferences. Purpose. This research aims to explore new media strategies for managing digital content in educational broadcasting, with a focus on optimizing content creation, distribution, and engagement across various digital platforms. Method. A qualitative research approach was employed, involving interviews with industry professionals and case studies of successful educational broadcasting programs. The study also analyzed digital content management practices in leading educational broadcasters and platforms. Results. The study found that successful educational broadcasters utilize a combination of adaptive content strategies, audience analytics, and interactive tools to manage digital content effectively. Key strategies included cross-platform content distribution, audience-driven programming, and the integration of real-time feedback mechanisms. Conclusion. The research concludes that new media strategies, such as adaptive content and data-driven decision-making, are crucial for enhancing the effectiveness of digital content management in educational broadcasting. Implementing these strategies can lead to more engaging and accessible educational experiences for a global audience.